Millimeter-wave high-gain SIW end-fire bow-tie antenna - Dadgarpour, Abdolmehdi; Zarghooni, Behnam; Virdee, Bal Singh; Denidni, Tayeb A. (IEEE, 2015)
This communication presents a high-gain bow-tie antenna that operates across 57–64 GHz for application in high data rate point-to-point communication systems. The proposed antenna consists of a pair of bow-tie radiators, where each radiator is etched on the opposite side of the common dielectric substrate and fed through substrate integrated waveguide (SIW) feed-line. The bow-tie radiators are arranged to cross each other symmetrically by tilting the feed-lines by 30◦ to enhance the antenna gain and to obtain the required radiation pattern. The antenna is loaded with a pair of double G-shaped resonators (DGRs) that are located in a region between the radiators and SIW to suppress the back-lobe level in the H-plane. Embedded in the E-plane of the antenna is an array of zero index metamaterial (ZIM) unit-cells whose purpose is to effectively confine the electromagnetic waves in the end-fire direction to enhance its gain performance. A prototype antenna was fabricated and its performance was measured to validate the simulation results. The proposed structure exhibits a gain of 11.8–12.5 dBi over the frequency range of 57–64 GHz with reflection coefficient less than −11 dB. In addition, the proposed antenna exhibits good cross-polarization, which is less than −17 dB in both E- and H-planes at 60 GHz.